Virus-like particles containing multiple antigenic proteins of Toxoplasma gondii induce memory T cell and B cell responses. - Su-Hwa Lee; Ki-Back Chu; Hae-Ji Kang; Fu-Shi Quan (PLoS ONE, 2019)
Although the efforts to develop vaccine against Toxoplasma gondii infection were made for decades, there is currently no licensed vaccine available for humans. Upon discovering a number of T or B cell epitope regions from T. gondii IMC, ROP18 and MIC8, multi-antigen VLPs or combination VLPs were generated. Mice immunized with multi-antigen VLPs or combination VLPs were challenge infected with T. gondii (ME49). T. gondii-specific IgG, IgG isotypes and IgA antibody responses, memory T and B cell responses and protection were evaluated. All the mice survived upon T. gondii challenge infection by multi-antigen VLPs vaccination. Vaccinated mice elicited higher levels of parasite-specific IgG and IgG2a antibody responses in sera, IgA antibody responses in feces, CD4+ and CD8+ T cell responses, and cytokines (IFN-γ, IL-10) responses compared to combination VLPs. In particular, the multi-antigen VLPs vaccination showed significantly higher levels of antibody secreting cell (ASC) responses, CD4+ and CD8+ effector memory T cells, and memory B cells than combination VLPs. Multi-antigen VLPs vaccination showed significant reduction of brain cyst counts and size, and all mice survived. Prediction and analysis of epitopes have indicated that IMC, ROP18 and MIC8 showed partially overlapping epitopes for T and B cells. Our results indicated that antibody responses, memory T and B cells induced by multi-antigen VLPs vaccination might contribute to the complete protection upon T. gondii (ME49) challenge infection.